2017
DOI: 10.3892/mmr.2017.6798
|View full text |Cite
|
Sign up to set email alerts
|

Scutellaria baicalensis Georgi induces caspase-dependent apoptosis via mitogen activated protein kinase activation and the generation of reactive oxygen species signaling pathways in MCF-7 breast cancer cells

Abstract: Scutellaria baicalensis Georgi extract (SBGE) is used in traditional herbal medicine and has also been used clinically to ameliorate the symptoms of various inflammatory diseases and cancer. In women, breast cancer is one of the most common diseases and numerous women succumb to it. The present study was undertaken to investigate the mechanism responsible for the SBGE‑induced apoptosis of MCF‑7 human breast cancer cells. SBGE was administered to cells at concentrations between 100 and 500 mg/ml, and cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…roots of Scutellaria baicalensis Georgi and is reported to have a series of pharmacological activities, including antioxidant, anti-inflammatory, antiviral, anti-human immunodeficiency virus and antitumor properties (17,(22)(23)(24)(25)(26)(27). However, to our knowledge, it has never been studied whether it may protect from arsenic toxicity.…”
mentioning
confidence: 99%
“…roots of Scutellaria baicalensis Georgi and is reported to have a series of pharmacological activities, including antioxidant, anti-inflammatory, antiviral, anti-human immunodeficiency virus and antitumor properties (17,(22)(23)(24)(25)(26)(27). However, to our knowledge, it has never been studied whether it may protect from arsenic toxicity.…”
mentioning
confidence: 99%
“… 53 Park's another research suggested that SBGE should be considered as an effective agent to inhibit the growth of breast cancer. 54 SBGE significantly induced the apoptosis of human breast cancer cells MCF-7 in the concentration range from 100 to 500 mg mL −1 . The 24 h treatment of SBGE for MCF-7 caused the inhibition of cell proliferation and increased the sub-G1 phase ratio.…”
Section: Anticancer Effects Of the Crude Polyphenols Of Skullcap Rootmentioning
confidence: 97%
“…It could reduce the expression of cyclin B1 and D1 by inhibiting protein synthesis and activation via proteasome degradation and inhibit the expression and activity of MMP-2 and MMP-9 mRNA. SBE can inhibit the proliferation of MCF-7 by inhibiting mitochondrial membrane potential, down-regulating Bcl-2/Bax [ 93 ]. SBE could downregulate the expression of caspase family members (e.g.…”
Section: Pharmacological Effects (Shown In Table 2 mentioning
confidence: 99%